Assessment of total annual effective doses to representative person, for authorised and accidental releases from the Nuclear Medicine Department at Cattinara Hospital (Trieste, Italy). (October 2022) - Signoriello, Michele; Fornasier, Maria Rosa; de Denaro, Mario; Arfelli, Fulvia; Santoro, Benedetta; Severgnini, Mara
Highlights: Liquid and solid waste management in Trieste Nuclear Medicine Department. Advanced screening models to assess discharged radioactivity into environment. Effective dose exposure to individuals according to Directive 2013/59/EURATOM. Assessing compliance with Italian Legislative Decree 101/2020. Accidental fire event in Radiopharmacy Laboratories simulated by HotSpot software. Abstract: Purpose: Clinical procedures in a Nuclear Medicine Department produce radioactive liquid and solid waste. Regarding waste release into the environment from an authorised hospital, it is mandatory to verify the compliance with European Directive 2013/59/EURATOM, adopted by the Italian Government via the Legislative Decree 101/2020. Methods: Different activity release pathways into the environment from Trieste Nuclear Medicine Department have been analysed: liquid waste from patients' excreta discharged by sewage treatment system into the sea, and atmospheric releases following solid waste incineration. Reference models, provided by NCRP and IAEA guidelines, have been implemented to assess the impact of the discharged radioactivity for coastal waters and atmospheric transport conditions. Finally, an accidental fire event occurring in Radiopharmacy Laboratories has been simulated by HotSpot software. Results: Advanced screening models give an effective dose to population of 5.3 · 10 −3  µSv/y and 1.4 · 10 −4  µSv/y for introduction by sewage system into coastal waters and atmospheric releases by the incinerator, respectively. Workers involved in the maintenance of the sewage treatment plant receive a total annual effective dose of 3.8 µSv/y, while for incinerator staff the total annual exposure is 5.9 · 10 −8  µSv/y. For the accidental fire event the maximum total effective dose to an individual results 3.8 · 10 −8 Sv with mild wind, and 4.1 · 10 −7 Sv with strong wind. Conclusions: The total annual effective doses estimated to representative person, due to both Nuclear Medicine authorised clinical practices and in case of an accidental fire event, are in compliance with regulatory stipulations provided by Directives.